Intravenous As2O3 as a promising treatment for psoriasis — an experimental study in psoriasis-like mouse model. (2nd November 2022) - Hao, Xiaoji; Liu, Xiaohui; Yu, Shunfei; Qin, Chang; Wang, Ruonan; Li, Chunna; Shao, Jing
Abstract: Objective: To evaluate the efficacy and mechanistic bases of the intravenous injection of arsenic trioxide at clinical-relevant doses for treating an imiquimod-induced psoriasis-like mouse model. Methods: After inducing psoriasis-like skin lesions on the back of mice with imiquimod, mice in each group were injected with a clinical dose of arsenic trioxide through the tail vein. The changes in the gene expression, protein expression and distribution of relevant inflammatory factors were evaluated in the inflicted skin area, for mechanisms underlying the efficacy of intravenous As2 O3 intervention. HaCaT cells were used to establish an in vitro psoriasis model and pcDNA3.1-NF-κB overexpression plasmid was transfected into cells to overexpress P65, which further confirmed the role of the NF-κB signaling pathway in the effectiveness of As2 O3 . Results: Clinical dose of As2 O3 can significantly improve abnormal symptoms and pathological changes in psoriasis-like skin lesions induced by IMQ in mice. While IMQ induced abnormal expression and distribution of inflammatory factors in the RIG-I pathway and the microRNA-31 (miR-31) pathway in psoriatic skin tissues, intravenous As2 O3 can effectively regulate and restore the normality. The leading role of NF-κB signaling was evidenced in vivo and validated in vitro using the NF-κB-overexpressed HaCaT cell model. Conclusion: Clinical dosage of As2 O3 may achieve effective treatment of IMQ-induced psoriatic skin lesions by modulating the NF-κB signaling pathway which regulates both the RIG-I and the miR-31 lines of action. Our data provided strong evidence supporting the claim that systemic As2 O3 administration of clinical doses can be a promising treatment for psoriasis patients.